Dynamic observation of the formation of melanocytic spheroids induced by repeated long-term trypsinization. - Huang, T.; Jin, H.; Zhang, R. (European Journal of Pediatric Dermatology, 2023)
Objective. To observe changes in the shapes and growth patterns of melanocytes (MCs) after receiving two long-term trypsinization (LTT) treatments for 2 hours each. Methods. Epidermal primary cells were obtained from foreskin tissues, which derived from routine circumcisions. Antibodies specific for keratin 15 (K15) and melanosomes (HMB-45) were used to identify keratinocytes (KCs) and MCs, respectively. MCs were purified via differential trypsinization, and then continued to be cultivated. When they became 70% confluent, the MCs were treated with LTT and were subcultured. After about 1 week, the above treatment was repeated. Changes in the morphologies and growth patterns of MCs were observed daily, were photographed and analyzed. Results. The results of immunofluorescence staining showed MCs presenting with dendrites and KCs with cobblestone-shapes coexisting in the epidermal cultures. MCs were purified by differential trypsinization and appeared as dendritic, in monolayer growth, with a doubling time of 3-5 d. After 2 h of LTT, those MCs proliferated more quickly with a doubling time of 2-3 d. Meanwhile, the number and length of dendrites were reduced, most of MCs were bipolar, and a few had three dendrites. After the second LTT, the MCs became short rod-shaped or fusiform, with a doubling time of less than 2 d. Some aggregates or spheroids of MCs gradually appeared and increased in size over the time of culture. Each MC spheroid (MS) contained 3-30 MCs, with various morphologies and sizes within the same spheroid. When MSs were picked up and re-seeded, the dendritic cells migrated out and expanded surrounding the spheroids. They proliferated rapidly, grew in a monolayer, and were morphologically similar to primary MCs. Conclusion. LTT reduced the number of dendrites and shortened the doubling time of MCs. Two repeat treatments of LTT can induce the formation of MSs.